Two Heads Writing Together, Is Collaborative Writing Better?: Exploring Students’ Perceptions - Siti Kholija Sitompul; Amira Wahyu Anditasari (Yayasan Visi Intan Permata, 2022)
Collaborative writing is considered an important skill in 21st-century learning, covering communication, creativity, and critical thinking. It has been proven to enhance students' writing skills. Therefore, this study aimed at investigating students' perceptions of collaborative writing. The perception was investigated through survey research by distributing a printed questionnaire to 31 students in grade ten at State Vocational School 1 of Portibi, North Sumatra. The questionnaire was a closed-ended version consisting of 11 questions, divided into meaningfulness and competence aspects. The questionnaire results were classified based on the Means scales, the Median, the Modes, and the Standard Deviation. The results showed the students' positive views (67.74%) regarding the usefulness of collaborative writing. The usefulness refers to the ease of constructing ideas, executing the writing process, understanding the concept of writing, and enhancing students' confidence. Additionally, students perceived the benefits of collaborative writing through discussion and peer review processes. They considered it as a meaningful process where they learned from their own and peers' mistakes. However, some students perceived it negatively since collaborative writing took more time than individual writing. Finding students' perceptions will be a reference for English teachers to improve the teaching writing through collaborative writing and find the strengths and weaknesses of collaboration. To acquire the usefulness and meaningfulness of collaborative writing, it was suggested that collaborative writing must be well acknowledged and designed based on students' conditions, level, and background.